Intentionality Analysis and Intersubjectivity - Bracken, Joseph A. (Horizons, 2006)
In Method in Theology Bernard Lonergan acknowledged the reality of intersubjectivity in human life and sought to incorporate it in various ways into his understanding of theological method. Building upon Lonergan's insights, this essay indicates how his three stages of meaning and different realms of meaning can be expanded in terms of the author's Neo-Whiteheadian metaphysics of universal intersubjectivity so as to justify a communal and processive approach to truth and objectivity in human affairs. In this way, Lonergan's transcendental method is clearly vindicated in a Neo-Whiteheadian as well as a Thomistic context and the resulting synthesis of metaphysical perspectives notably strengthens the position of those who advocate discussion and dialogue over the use of force for the resolution of persistent controversial issues.